Recent advances in the management of chronic pain. Issue 2 (February 2017) - Stewart, Kate
Abstract : Current treatments for chronic pain are often ineffective and are associated with some problematic side‐effects. This article discusses some new approaches that may offer better treatment options for patients with chronic pain in the future.